EFFECTIVENESS OF ORALLY USE TILAPIA (Oreochromis niloticus) ON WOUND LENGTH AND FIBROBLAST DENSITY ON INCISION WOUND OF WISTAR RAT (Rattus norvegicus) - Sayyidah Vina Syauqia; A Fariz Malvi Zamzam Zein; Tiar M Pratamawati; Donny Nauphar (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: The incidence of a wound in Indonesia has increased from 7.5 percent in 2007 to 8.2 percent in 2013 according to Riskesdas. Wound care that widely used is povidone-iodine, but in case, it has a toxic effect on healthy cells around the wound. The albumin, amino acids, and fatty acids in Tilapia (Oreochromis niloticus) are the potential substances to accelerate the wound healing process. This study aims to investigate the efficacy of Tilapia (Oreochromis niloticus) on wound length and fibroblast density on the incision wound of Wistar rat (Rattus norvegicus).Methods: The study was conducted in the Food and Nutrition PAU Laboratory and Pathology Anatomy Laboratory of Universitas Gadjah Mada, Yogyakarta. This post-test only control group design experimental study used 30 male white rats that randomly divided into five groups, i.e. control group K, and treatment group P1, P2, P3 and P4 that were each given Tilapia with a dose of 12.5 mg/200gBW, 25 mg/200gBW, 37.5 mg/200gBW dan 50 mg/200gBW. The length of the wound was measured by a ruler each day. The rats were terminated on the 10th day to obtain wound tissue for H&E stained histopathological sections to observe fibroblast density. One Way ANOVA, Tamhane, Kruskal-Wallis and Mann Whitney tests were used to compare the wound length and fibroblasts density.Results: Incision wounds in this study showed the best wound healing on the 10th day. Based on the theory, on the 10th day, a proliferation and remodeling phase occurs. There is an effect of giving Tilapia (Oreochromis niloticus) orally at a different dose. Tilapia at dose 37.5mg/200gBW is more effective compared with the dose of 12.5mg/200gBW, 25mg/200gBW, and 50mg/200gBW to accelerate wound healing for wound length and fibroblast density in Wistar rat (Rattus norvegicus).Conclusion: Consuming Tilapia (Oreochromis niloticus) could be a new alternative for wound healing treatment. The antimicrobial ability of Tilapia should be analyzed.